The role of water and energy use in expanding the boundaries of irrigated agriculture in the Berrechid plain of Morocco. (11th May 2022) - Ouassissou, Romaissa; Lacombe, Guillaume; Kuper, Marcel; Hammani, Ali; El Amrani, Mohamed
Abstract: Despite the attention given to the water–energy–food nexus, there is little field evidence of how this plays out for irrigators. This article analyses the diversity of irrigation system configurations and their related water and energy use in semi‐arid Morocco, where groundwater‐fed and pressurized drip irrigation, although supposedly thrifty, is energy intensive. The analysis relying on hydraulic calculations and multiple linear regressions was based on interviews, observations and measurements on irrigation systems in 25 farms. The results show that each farmer used between one and three pumps and up to two storage reservoirs to pump groundwater from up to 120 m deep borehole(s) and transfer it along a distance often exceeding 2 km to reach available fertile lands that are rented. Such distances had little effect on the system‐wise energy consumption, varying between 4.62 and 4.88 kWh m −3, although the recycled car engines powering these irrigation systems were largely inefficient, consuming on average 2.5 kWh m −3 . State subsidies encourage these water‐intensive and energy‐inefficient farming systems, increasing pressure on groundwater and land. These findings underline the importance of going beyond a strict nexus perspective, as expansion of the 'groundwater economy' is accompanied by conflicts over tenure and increasing inequalities in access to water that threaten the sustainability of irrigated agriculture. Résumé: Malgré une attention croissante accordée au nexus eau–énergie–alimentation, peu de travaux ont montré comment il se traduit pour les irrigants. Cet article analyse la diversité des systèmes d'irrigation et comment ils influencent l'utilisation de l'eau et de l'énergie dans le Maroc semi‐aride où l'irrigation goutte‐à‐goutte par l'eau souterraine, théoriquement économe en eau, est énergivore. Des données sur les systèmes d'irrigation et les consommations d'eau et d'énergie, collectées par des entretiens, des observations et des mesures dans 25 exploitations agricoles, ont été analysées au moyen de calculs hydrauliques et de régressions linéaires multiples. Les résultats montrent que chaque agriculteur utilise entre une et trois pompes, et jusqu'à deux bassins de stockage d'eau, pour pomper l'eau de forages pouvant atteindre 120 m de profondeur, et la transférer sur plusieurs kilomètres, afin d'atteindre des terres fertiles prises en location pour l'irrigation. Ces distances s'avèrent n'avoir que peu d'effet sur la consommation énergétique de chaque système, variant entre 4.62 et 4.88 kWh m −3, mais les moteurs de voiture recyclés utilisés pour ces pompages sont largement inefficients, consommant en moyenne 2.5 kWh m −3 . La résultante pression sur les ressources en eau souterraines et les terres disponibles, et l'inefficience énergétique de leur irrigation, sont accentuées par les subventions étatiques. L'expansion de l'agriculture irriguée intensive s'accompagne d'arrangements fonciers conflictuels et d'inégalités croissantes dans l'accès à l'eau conditionnant la durabilité de ces systèmes et démontrant l'intérêt d'analyses qui dépassent la stricte perspective de nexus.